Evaluation of tubal and peritoneal factors in chlamydia positive infertile women by laparoscope (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Abnormalities or damage to the fallopian tube interferes with fertility and is responsible for abnormal implantation (eg, ectopic pregnancy). Obstruction of the distal end of the fallopian tubes results in accumulation of the normally secreted tubal fluid, creating distention of the tube with subsequent damage of the epithelial cilia (hydrosalpinx). Genital Chlamydia trachomatis infection has a worldwide distribution6 and is now recognized as the single most common cause of tubal peritoneal damage. The study explores the relationship between serum chlamydia antibody titres (CATs) and detection of tubal damage in infertile women.Objective: To Evaluation of tubal and peritonial factors in chlamydia positive infertile women by laparoscope.Methodology: The tubal status and pelvic findings in 138 women underwent laparoscopy for infertility were related to CAT, which was measured using the whole-cell inclusion immunofluorescence test. RESULTS: A total of 138 infertile women who underwent laparoscopic investigation for infertility were identified and they were divided in two groups, on the bsis of presence is absence Chlamydia positive (n=69) and Chlamydia Negative (n=69). Demographic status were almost similar between two groups, however service holder was found significantly higher in Chlamydia positive group (17 vs. 7). Tubal block was found in 44(63.7%) in Chlamydia positive and 37(53.6%) in Chlamydia negative. The difference was statistically significant (p